الشرود الذهني لدى طلبة المرحلة الثالثة في كليات التربية - حسن، زينب ثائر; الياسري، نداء محمد باقر (جامعة البصرة - كلية التربية للعلوم الإنسانية, 2023)
يهدف البحث الحالي إلى: 1- التعرف على مستوى الشرود الذهني لدى طلبة المرحلة الثالثة في كليات التربية في جامعة البصرة. 2- التعرف على مستوى الشرود الذهني لدى طلبة المرحلة الثالثة في كليات التربية في جامعة البصرة وفقاً لمتغير الجنس والتخصص وتكون مجتمع الدراسة من طلبة المرحلة الثالثة في كليات التربية البالغ عددهم (۲۲۲۳)، وبلغ حجم العينة الدراسية (۲۲۲) طالباً وطالبة، منهم (۱۳۹۱) طالباً وطالبة توزعوا على التخصصات الإنسانية، و(۸۳۲) طالباً وطالبة توزعوا على التخصصات العلمية، وكان مجتمع الذكور بواقع (٤٦٩) طالباً توزعوا على جميع التخصصات وكان مجتمع الإناث يبلغ (١٧٥٤) توزعن على التخصصات كافة، وقد عالجت الباحثتان نتائج البحث باستخدام الاختبار التائي لعينه واحده وتحليل التباين الثنائي وأظهرت النتائج أن عينة البحث تمتلك مستوى عالي من الشرود الذهني ولا توجد فروق معنوية بين الذكور والإناث في مستوى الشرود الذهني كذلك لا توجد فروق معنوية بين التخصصات العلمية والإنسانية في مستوى الشرود الذهني. وفي ضوء نتائج البحث قدمت الباحثتان عدد من التوصيات والمقترحات. The current study aims at: 1- Identifying the level of mental wandering among third-year students in the colleges of education at the University of Basrah. 2- Identifying the level of mental wandering among third-year students in the colleges of education at the University of Basrah according to the variable of gender and specialization. The study population consisted of (2223) third-year students in the colleges of education, and the size of the study sample was (222) male and female students, of whom (1391) male and female students were distributed among the specializations of humanities, and (832) male and female students were distributed among the scientific specializations. Males, with (469) students distributed among all specializations, and the female population amounted to (1754) distributed among all specializations, and the two researchers treated the results of the research using one-sample T-test and binary variance analysis. The results showed that the research sample has a high level of mental wandering and there are no significant differences between males and females in the level of mental wandering. Also, there are no significant differences between the scientific and humanitarian specializations in the level of mental wandering. In light of the results of the research, the two researchers presented a number of recommendations and suggestions.
Keywords: الشرود الذهني -- طلبة الجامعات -- السلوك الإنساني -- العراق